Corruption and Illicit Financial Flows in Nepal - Bhusal, Tara Prasad (Tribhuvan University Journal, 2016)
In recent years, considerable intellectual interest has arisen over the extent of illicit financial flows which may have development, governance or other consequences for both developed and developing countries. Illicit financial flows involve the cross-border transfer of the proceeds of corruption, trade in contraband goods, criminal activities, and tax evasion. The main objective of this article is to explore the current situation of illicit financial flows from the developing countries with special reference to south Asia and Nepal. The article also explains its causes, impact and measures to stem those flows. Although much effort and resources have been used to stem the illicit financial flows in the world, it is in increasing trend specially in case of developing world.